ANALISIS SIKAP DAN KEPUASAN PETANI TERHADAP ATRIBUT ASURANSI USAHATANI PADI DI KABUPATEN KARAWANG JAWA BARAT - Mega Mustika; Anna Fariyanti; Netti Tinaprilla (Forum Agribisnis, 2019)
Agricultural sector technically has quite high risk of uncertainty, including crop failure level which is caused by climate change, pest attack and disease, flood, dryness, as well as price uncertainty which is at the end harm the farmer. In order to decrease the risk that faced by farmers especially rice farmer, government run Asuransi Usaha Tani Padi (AUTP) program. This research aimed to analyze the farmer’s attitude and satisfaction to AUTP attributes in Karawang West Java. Analysis tools that used in this research are Multiatribut Fishbein analysis to observe farmer’s attitude and Customer Satisfaction Index (CSI) analysis to detect farmer’s satisfaction level to AUTP attribute. The result of this research, found that the most important attributes according to farmer based on the importance level are Penyuluh Pertanian Lapangan (PPL), the number of the claim, direct socialization, farmer group leader and easy access to information. Farmer’s satisfaction level to AUTP attributes overall is quite satisfy. Therefore the performance of AUTP attributes level need to be increased, so that the farmer’s attitude and satisfaction to AUTP increase. Farmers that have positive attitude and satisfaction tend to follow the program continously and will recommend it to other farmer.